Characterization and genetic inheritance of temperature sensitive genetic male sterility in desi cotton (Gossypium arboreum) - SANTHY, V; PALVE, S M; VIRKHEDE, SONALI; MOHAN, PRATIBHA; KHADI, B M (The Indian Journal of Agricultural Sciences, 2026)
The two line method of temperature sensitive genetic male sterility (TGMS) is a useful method for production of hybrid seed in crop plants. TGMS 1-1 line has been identified, characterized and stabilized in desi cotton (Gossypium arboreum L.). It was completely male sterile under high minimum temperature of summer months and exhibited complete pollen fertility under low temperature condition. The Critical Sterility Point was determined as 24°C minimum temperature and 40°C maximum temperature with continuous sunshine and Critical Fertility Point was determined as 18°C minimum and 33°C maximum temperature. The inheritance studies revealed that the trait is governed by single recessive gene. The TGMS 1-1 line developed and characterized was found useful for hybrid seed production in May (100% male sterile) when the minimum temperature was above 24°C and for maintenance when sown in the normal kharif by selfing.